Prevalence and reasons for referrals to the Endodontics Specialty Clinic at the Piracicaba Dental School - Jéssica Rodrigues RAMOS; Juliana Delatorre BRONZATO; Eloa Cristina BICEGO-PEREIRA; Adriana DE-; Marina Angelica MARCIANO; José Flávio Affonso ALMEIDA; Caio Cezar Randi FERRAZ; Brenda Paula Figueiredo de Almeida GOMES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Dental referrals to the Endodontics Specialty Clinic (ESC) are routine owing to the complexity of endodontic treatments. To obtain a better prognosis for treatment, students/dentists must perceive their technical limits. This study sought to investigate the referrals of patients to the ESC from different clinics of the Piracicaba Dental School, State University of Campinas - SP, Brazil, and check: a) the demographic profile of patients and the most commonly affected tooth; b) the clinic with the largest number of referrals; c) the reasons for referrals; d) the complexity of the cases; e) and the difficulty in assessing the referred cases based on the classification provided by the American Association of Endodontists (AAE) and Souza-Filho. The study sample consisted of patients' electronic dental referral records from February 2015 to June 2019. A total of 1,707 patients were referred to the ESC during the study period, and 62.4% were female. Lower molars were the most frequently involved teeth (34.8%), and 60.7% of the cases were referred due to the presence of root curvature. The AAE classification showed prevalence of highly difficult cases (71.3%), whereas Souza-Filho classification demonstrated a high rate of class III cases (85.8%). This study highlights the difficulties encountered by undergraduate students before or during endodontic treatments, reinforcing the need for clear criteria for selecting cases appropriate for each education level, thus improving endodontic treatment prognosis.